De la déstructuration de l’intime à l’unicité spirituelle : l’« espace de l’enquête » dans la littérature et l’iconographie religieuses de l’Espagne des XVIe et XVIIe siècles - Marcela Rivas-Jamett (E-Spania)
The modalities and representations of intimate and intimacy in the Golden Age in religious literature and iconography, give rise to a reflection on the modus operandi of the ecclesial institution. The interpretation of the Holy Scriptures, the examination of conscience and resignation were to converge in the fear of death and modify the corporeal hexis. The intimate became, according to Jean-Claude Passeron's expression, the "space of inquiry", "a universe of solidary meanings", having as its purpose to destructure the impenetrable psyche, to erect its reasoning in "truthfulness", to profoundly constrain the cognitive system, in order to obtain massive adherence to the doctrine then in force. This will involve analysing the annihilation of the intimate, the impact of symbolic representations and their expression in the public space, which enable to exacerbate the spiritual uniqueness.